2019
DOI: 10.29185/hayuretim.458620
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Diagnosis in Dairy Cattle

Abstract: Sütçü sığırlarda erken gebelik tanısı reprodüktif yönetim açısından oldukça önemlidir. Erken gebelik tanısı, gebe olmayan hayvanların zamanında tedavi edilmeleri ve yeniden tohumlanmaları yoluyla buzağılama aralığındaki uzamayı engeller. Suni tohumlamadan sonraki 18 -24 günler arasında östrusa gelme, gebe olmayan hayvanların tespit edilmesindeki en kolay yöntemdir. Rektal palpasyon ve transrektal ultrasonografi erken gebelik tanısı amacıyla en sık kullanılan klinik yöntemlerdir. Progesteron veya gebelikle iliş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Pregnancy-associated glycoproteins (PAG) aresynthesized in the mono-and binucleate cells of the ruminant's trophectoderm (Sousa et al, 2006). PAG can be used for pregnancy diagnosis in ruminants by detecting their presence or concentrations in the maternal blood circulation (Akköse and Cebi-Sen, 2019;Chaves et al, 2017;Silva et al, 2007;Singh et al, 2021). de Carolis et al (2020), reported that the cutoff value of PAG concentrations (radioimmuno assay, RIA-706 and RIA-srPool) are ≥ 1.0 ng/mL in order to distinguish between pregnant and nonpregnant Sarda and Lacaune ewes.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-associated glycoproteins (PAG) aresynthesized in the mono-and binucleate cells of the ruminant's trophectoderm (Sousa et al, 2006). PAG can be used for pregnancy diagnosis in ruminants by detecting their presence or concentrations in the maternal blood circulation (Akköse and Cebi-Sen, 2019;Chaves et al, 2017;Silva et al, 2007;Singh et al, 2021). de Carolis et al (2020), reported that the cutoff value of PAG concentrations (radioimmuno assay, RIA-706 and RIA-srPool) are ≥ 1.0 ng/mL in order to distinguish between pregnant and nonpregnant Sarda and Lacaune ewes.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In fact, PAGs are thought to be involved in maternal recognition of pregnancy. 8 Presence of PAGs in maternal circulation allows for an early diagnosis of pregnancy, 9,10 detection of late embryonic or early fetal deaths, identification of twin pregnancies, and monitoring of placental function. 11,12 Also, early detection of non pregnant animals permitsa prompt reintoduction to appropriate reproductive management practices thereby reducing the calving interval.…”
Section: Introductionmentioning
confidence: 99%